2014
DOI: 10.1002/oby.20959
|View full text |Cite
|
Sign up to set email alerts
|

The weight of stigma: Cortisol reactivity to manipulated weight stigma

Abstract: Objective: Rates of weight-based stigmatization have steadily increased over the past decade. The psychological and physiological consequences of weight stigma remain understudied. Methods: This study examined the effects of experimentally manipulated weight stigma on the stressresponsive hypothalamic-pituitary-adrenal axis (HPA) in 110 female undergraduate participants (BMI: M 5 19.30, SD 5 1.55). Objective BMI and self-perceived body weight were examined as moderators of the relationship between stigma and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 37 publications
8
135
2
3
Order By: Relevance
“…They show that experimental manipulations that aim to induce experiences of weight stigma lead to behavioral and physiological changes, including increased unhealthy eating (Incollingo Rodriguez, Heldreth, & Tomiyama, 2016) and cortisol secretion (Himmelstein, Incollingo, & Tomiyama, 2015), which in the long-term could promote physiological dysregulation.…”
Section: Perceived Weight and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…They show that experimental manipulations that aim to induce experiences of weight stigma lead to behavioral and physiological changes, including increased unhealthy eating (Incollingo Rodriguez, Heldreth, & Tomiyama, 2016) and cortisol secretion (Himmelstein, Incollingo, & Tomiyama, 2015), which in the long-term could promote physiological dysregulation.…”
Section: Perceived Weight and Healthmentioning
confidence: 99%
“…Importantly, the stress-induced physiological consequences of weight stigma are most pronounced among those who perceive themselves as heavy (Himmelstein et al, 2015).…”
Section: Perceived Weight and Healthmentioning
confidence: 99%
“…Second, a qualitative study framed within SSPT identified being seen in a bathing suit by others as the most uncomfortable situation (Lamarche et al, 2012)-being in a bathing suit or increasing the level of body exposure has been an important aspect of manipulations designed to elicit body image concerns (Carron & Prapavessis, 1997;Gammage et al, 2004;Hart et al, 1989;Martin Ginis et al, 2012). Third, anticipation of this specific threat has been shown to elicit social physique anxiety and body shame responses (Cloudt et al, 2014;Lamarche et al, 2014), thus it is possible that actually exposing an individual to this threat would also elicit a cortisol response, similar to responses to a weight stigma situation (Himmelstein et al, 2015). Fourth, a skinfold assessment was originally used to validate a questionnaire measuring social physique anxiety (Hart et al, 1989).…”
mentioning
confidence: 99%
“…Women exposed to weight-based stigmatizing stimulus experienced an increase in cortisol secretion, regardless of their weight (Himmelstein, Incollingo & Tomiyama, 2015;Schvey, Puhl, & Brownell, 2014). In other words, women across a range of BMI levels, from thin to obese, demonstrate negative physiological responses to weight-based stigma; stress reactions to weight-based stigma related more strongly to the women's perceived weight status, rather than to their actual BMI measure.…”
Section: Fat-shaming Is Stressfulmentioning
confidence: 99%